Developing English materials for English for tourism - Muhamad Argi Afriandi; Nur Fatimah (Universitas Ahmad Dahlan)
The potential of tourism industry increases every year. The tourism sector is believed to be able to create centers of economic growth of the country. One of the institutions that play a role in tourism industry is English Education Department, Universitas Ahmad Dahlan. This department cooperates with several tourism partners to train the students about tourism. There are two subjects about tourism named English for Tourism and Practicum on Tourism. The problem emerged from the students and materials. The students of English for Tourism lack of vocabulary and speaking. They need specific materials (textbook) for learning English about tourism. The materials of English for Tourism should be developed. Therefore, the objectives of the study are (1) developing English materials for English for Tourism; (2) finding out the possible English developed materials for English for Tourism. This study is research and development. The steps are identifying potentials and problems, collecting the data, product design, product validation, product revision and product trial. The data were obtained from an instrument of which validation was from an expert of material, instrument expert. The validated instrument was used for subject trial assessment. The subject of this research was the students of English for Tourism. Simple random sampling was used in this study. In composing the materials, the needs from the previous research by Effendi and Khafidhoh (2018) were one to consider in addition to the existing syllabus of English for Tourism in English Education Department. The product of this research is English developed materials (textbook) for English for Tourism. The total score of expert material’s validation is 82%, it shows that the developed materials are excellent. The mean of subject trial assessment is 82.94%, it shows that the product is excellent. The mean of the score validation and subject trial assessment is 82.47%, it is an excellent product.